Effect of Beach-Chair Position on Cerebral Blood Flow in Patients Undergoing Shoulder Surgery—A Preliminary Observational Study - Antony, Jesudoss; Singh, Georgene; Yadav, Bijesh; Abraham, Melvin A.; George, Sajan P. (Journal of Neuroanaesthesiology and Critical Care, 2021)
Background Hypotension and cerebral hypoperfusion, commonly encountered in beach-chair position under general anesthesia, carry the risk of neurologic complications. There is a paucity of data on monitoring cerebral perfusion. Our objective was to compare the mean arterial pressure (MAP) and middle cerebral artery velocity (Vmca) in the supine and beach-chair position and estimate its correlation during hypotension.Materials and Methods Twenty ASA class I and II patients undergoing elective shoulder surgery in beach-chair position were included in the study. MAP was measured invasively with the pressure transducer leveled to the phlebostatic axis. Vmca was measured with a 2 MHz transcranial Doppler (TCD) probe through the temporal window. Both MAP and Vmca were measured at baseline after anesthetic induction in the supine position (BL), on assuming the beach-chair position (AP), at steady-state hemodynamics in beach-chair position (P1), whenever there was a drop in MAP > 20% (P2), and on the restoration of MAP (P3).Results A mean decrease in MAP and Vmca by 24.76% and 27.96%, respectively, from supine to beach-chair position with a significant linear correlation between MAP and Vmca along with a Pearsons' coefficient of 0.77 was seen. A change in MAP of 1 mm of Hg resulted in a change in Vmca by 0.53 cm/sec (p < 0.05).Conclusion A significant decrease in MAP and Vmca was observed in the beach-chair position. TCD could be used as a point-of-care noninvasive technique to reliably assess cerebral perfusion.
Keywords: cerebral blood flow velocity; beach chair position; transcranial doppler